"Still doing it by hand": Auden and the typewriter - Sullivan, H (Palgrave Macmillan, 2015)
W. H. Auden's writing practice remained the same across his life: he composed first drafts by hand, revised by hand, and only used a typewriter for typing up a late draft. By the 1950s, this was not merely a habit, it was also a medially conservative position. This chapter explores Auden's commitment to hand-writing alongside the formal and aesthetic choices of his late poetry.